Policy Design of Scenarios for the National English Program - Tumpasuwan, Rattanapong; Xupravati, Penvara; Kulophas, Dhirapat (CRMA Journal of Humanities and Social Sciences, 2025)
This research was conducted to envision the future of academic administration for the English Program (EP) based on the concept of International mindedness, and to prepare for global transformations in the coming decades. This study was conducted using a qualitative approach, incorporating the process of foresight research through three key steps: (1) Studying conceptual frameworks related to international mindedness and academic administration in the English Program; (2) Horizon scanning to identify emerging trends and key driving forces that may impact the future; and (3) Scenario building through a future foresight workshop involving 16 selected stakeholders and experts in English Program administration. These participants included: (1) National education policy-makers; (2) Academic scholars; (3) School leaders from English Programs under the Office of the Basic Education Commission (OBEC); (4) School leaders from English Programs under the Office of the Private Education Commission (OPEC); (5) English Program heads from OBEC-affiliated schools; (6) English Program heads from other educational organizations; (7) Parents; and (8) Alumni representatives. Through small-group workshops and qualitative analysis, the research produced four future scenarios of English Program academic administration over the next decade: (1) EP Opportunity Nation; (2) The Human Advantage EP; (3) Blueprint-Based EP Reform; and (4) Bridge the Gap EP. After developing and presenting these four scenarios, the experts engaged in a critical analysis of each scenario's attributes, strengths, weaknesses, opportunities, and risks, to identify the preferable future for English Program academic administration. The selected preferable future was then used as a foundation for designing actionable policy recommendations to support the sustainable development of the English Program in alignment with future global challenges.